Spatial heterogeneity affecting fish fauna in cascade reservoirs of the Upper Parana Basin, Brazil - Ferrareze, Mateus [UNESP]; Casatti, Lilian [UNESP]; Nogueira, Marcos G. [UNESP] (Springer, 2014)
In cascade reservoirs, different zonation effects can be observed along the longitudinal axis, depending on the retention time of each reservoir. In this study, we evaluated the relationships among fish and spatial and environmental variables across longitudinal zones within reservoirs with different retention times. Fieldwork was carried out during two periods in three different zones that represent the longitudinal axis (lotic, transitional, and lentic) of three reservoirs. Each reservoir has different retention times (low, intermediate, and high) and all are located in a cascade system of the Paranapanema River, Brazil. In the high retention time reservoir, richness, biomass, and diversity decreased along the longitudinal axis, in contrast to the numerical abundance and dominance. Conversely, in the low retention time reservoir, these community attributes varied in an opposite way. Both spatial (depth, retention time, longitude, and latitude) and environmental (dissolved oxygen, water temperature, Secchi disk, total nitrogen) variables were important controlling factors for fish communities in reservoirs, which confirms the hypothesis that reservoir retention times create a zonation effect with different proportions along the main axis, resulting in a spatial heterogeneity with specific environmental features, and it determines the fish assemblage structure and composition in each reservoirs.
Keywords: Ichthyofauna; Zonation; Lentic ecosystem; Retention time; Limnology